2017
DOI: 10.1016/j.exer.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

PERK and XBP1 differentially regulate CXCL10 and CCL2 production

Abstract: Inflammation plays a key role in the pathogenesis of many retinal degenerative diseases related with photoreceptor dysfunction/degeneration. However the involvement of photoreceptor cells in inflammatory reactions is largely unknown as they are not considered as inflammatory cells. In this study, we assessed whether photoreceptor cells can produce CCL2 and CXCL10, two important players in inflammation during endoplasmic reticulum (ER) stress. After photoreceptor 661W cells were treated with ER stress inducer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 90 publications
(124 reference statements)
3
13
0
1
Order By: Relevance
“…In addition, MCP‐1 secretion is reduced by SAL in gLDL‐exposed HEC. Reported data show that eIF2α/CHOP pathway activated by ERS is important for the stimulation of VCAM‐1 and MCP‐1 production in other experimental models . Interestingly, in agreement with these studies, we have previously revealed that in HEC after 24 h incubation with gLDL, only eIF2α/CHOP pathway of the unfolded protein response remains upregulated .…”
Section: Discussionsupporting
confidence: 84%
“…In addition, MCP‐1 secretion is reduced by SAL in gLDL‐exposed HEC. Reported data show that eIF2α/CHOP pathway activated by ERS is important for the stimulation of VCAM‐1 and MCP‐1 production in other experimental models . Interestingly, in agreement with these studies, we have previously revealed that in HEC after 24 h incubation with gLDL, only eIF2α/CHOP pathway of the unfolded protein response remains upregulated .…”
Section: Discussionsupporting
confidence: 84%
“…These data indicate that ZIKV can effectively infect and replicate in Müller cells. As a comparison, we infected human retinal microvascular endothelial cells (HRMECs) and mouse retinal photoreceptor cells (661W cells (Zhu et al, 2017)) at a higher MOI of 0.2. Similar to Müller cells, ZIKV viral RNA in HRMECs was detected at day 1 and increased at day 4 after infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we next treated cells at day 3 post infection with the inhibitors for ERK (PD98059), p38MAPK (SB202190), NF-κB (PDTC), STAT3 (Stattic) and JAK1/JAK2 (AG490), and determined their effects on ZIKV-induced inflammatory and growth factors. Since endoplasmic reticulum (ER) stress and NADPH oxidase have been shown to regulate the activation of these kinases and transcription factors in response to different stimuli (Valadao et al, 2016; Zhang et al, 2009; Zhu et al, 2017), the inhibitors for ER stress and NADPH oxidase were also included: TUDCA and PBA–chemical chaperones blocking ER stress, GSK2606414–inhibitor of ER stress branch PERK, 4μ8C–inhibitor of ER stress branch IRE1, and apocynin–inhibitor of NADPH oxidase. Most inhibitors were not toxic to cells, while PBA, 4μ8C and Apocynin slightly reduced Müller cell viability as determined by MTT assay (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations